Strategi Pengembangan Bisnis Dengan Menggunakan Matriks Ansoff Pada Bank Mandiri Cabang Banjarnegara - Sabana, Hesti; Ismaya, Nesha; Nandisa, Alfath Shofa; Shafrani, Yoiz Shofwa (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This research discusses the business development strategy of Bank Mandiri Banjarnegara Branch using Ansoff Matrix as the main analysis tool. The issue raised is how this branch designs and implements growth strategies amidst banking industry competition and local challenges, such as limited digital infrastructure and customer characteristics. The research objective was to describe the implementation of the four Ansoff Matrix strategies, namely market penetration, market development, product development, and diversification, in the context of branch operations. Qualitative descriptive research was used, with data collection through interviews, observation, and documentation. The results showed that Bank Mandiri Banjarnegara Branch implemented market penetration strategy through active promotion and service improvement, market development strategy by cooperating with customers as mini ATM partners, product development strategy through customer needs survey, and diversification strategy with strict risk mitigation. The conclusion of this study confirms that the application of Ansoff Matrix in a structured manner is able to assist branches in facing competition and optimizing business growth opportunities in non-metropolitan areas.